2019
DOI: 10.1002/esp.4718
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional turbulent structures at a medium‐sized confluence with and without an ice cover

Abstract: River confluences are characterized by a complex mixing zone with three‐dimensional (3D) turbulent structures which have been described as both streamwise‐oriented structures and Kelvin–Helmholtz (KH) vertical‐oriented structures. The latter are visible where there is a turbidity difference between the two tributaries, whereas the former are usually derived from mean velocity measurements or numerical simulations. Few field studies recorded turbulent velocity fluctuations at high frequency to investigate these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 50 publications
4
26
0
Order By: Relevance
“…More measurements of mixing rates and patterns at particular confluences over a suite of flow conditions are needed, and studies that assess mixing at numerous confluences are also recommended. Because of the difficulty in measuring detailed cross‐sectional velocities, studies that assess mixing at many confluences may benefit from remote sensing and noncontact methods to determines patterns of flow and mixing, at least at the surface (Biron et al, 2019; Lewis & Rhoads, 2018a, 2018b). However, as this study has shown mixing can be highly three‐dimensional, especially when influenced by helical motion of the flow.…”
Section: Discussionmentioning
confidence: 99%
“…More measurements of mixing rates and patterns at particular confluences over a suite of flow conditions are needed, and studies that assess mixing at numerous confluences are also recommended. Because of the difficulty in measuring detailed cross‐sectional velocities, studies that assess mixing at many confluences may benefit from remote sensing and noncontact methods to determines patterns of flow and mixing, at least at the surface (Biron et al, 2019; Lewis & Rhoads, 2018a, 2018b). However, as this study has shown mixing can be highly three‐dimensional, especially when influenced by helical motion of the flow.…”
Section: Discussionmentioning
confidence: 99%
“…However, based on drone imagery, Biron et al. (2019) observed that only KH vortices dominated within the shear layer for discharge ratios ranging from 0.09 to 1.02 in a medium‐sized confluence. Twin surface‐convergent helical cells were observed on either side of the shear layer in a vertical plane, which rapidly evolve into a single, channel‐scale circulation cell due to the differences in the curvature of the two combining flows (Bradbrook et al., 2000; Rhoads & Kenworthy, 1995, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The shear layer characterized by von Kármán vortex street for the momentum ratios close to unity, that is, wake mode (Constantinescu et al, 2011(Constantinescu et al, , 2012 or vortex pairing for those far from unity, that is, KH vortices dominating mode (Rhoads & Sukhodolov, 2004) were reported. However, based on drone imagery, Biron et al (2019) observed that only KH vortices dominated within the shear layer for discharge ratios ranging from 0.09 to 1.02 in a medium-sized confluence. Twin surface-convergent helical cells were observed on either side of the shear layer in a vertical plane, which rapidly evolve into a single, channel-scale circulation cell due to the differences in the curvature of the two combining flows (Bradbrook et al, 2000;Rhoads & Kenworthy, 1995.…”
mentioning
confidence: 99%
“…Transverse mixing due to molecular diffusion is usually negligible compared to shear dispersion and advective effects over a range of spatial scales. Mixing is due firstly to the shear between the two incoming flows, characterized by turbulent eddies that develop at the mixing layer scale (Biron et al, 2019) and substantially enhance transverse mixing in the near-field downstream of the confluence. In addition to shear dispersion, mixing may be enhanced by convective effects due to large-scale, persistent flow structures, notably, helical motion and upwelling motion.…”
Section: Introductionmentioning
confidence: 99%